Hellbound Saint: A Novel Exploring the Impacts of Domestic Violence on Children and Their Long-term Effects - Jane Patricia Wijaya; Liem Satya Limanta (Kata Kita: Journal of Language, Literature, and Teaching, 2025)
Domestic violence is a situation where abuse occurs in a household setting and witnessing it during childhood may lead to childhood trauma. Such trauma might linger until adulthood, and manifest in various ways including general or complex Post-Traumatic Stress Disorder (PTSD) and psychopathic traits. This thesis will analyze the impacts of domestic violence using the complex trauma framework by Julian D. Ford and Christine A. Courtois. The creative work will be a psychological thriller novel, depicting Raisya and Yohan’s trauma journey due to witnessing domestic violence during childhood. Raisya’s trauma manifests as complex PTSD, while Yohan’s manifests as psychopathy tendencies.